PERAN MODAL SENDIRI DAN MODAL PINJAMAN PADA PEROLEHAN SISA HASIL USAHA - Fandil Famdil; Zumrotun Nafi`ah; Herlina Wati (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract The remaining operating results and special reserves are the determinants for calculating the turnover of capital, both own capital and loan capital. The purpose of this study was to determine whether the remaining amount of operating income would be influenced by own capital and loan capital in the KPRI "SIBUNDA" Cooperative. The sample of this research is financial statements and balance sheet reports from 2018 to 2020 at KPRI "SIBUNDA" located in Bojonegoro Regency. The results of this study indicate that simultaneously or partially own capital and loan capital have an effect on the acquisition of the remaining operating results. The more the amount of own capital, the greater the remaining operating results and conversely the less capital, the less the remaining operating results.